AKIBAT HUKUM TERHADAP HAK MASYARAKAT ADAT DALAM PERALIHAN AGAMA DI DESA ADAT DALUNG - Ida Bagus Putu Eka Suadnyana; I Wayan Titra Gunawijaya (PARIKSA: Jurnal Hukum Agama Hindu, 2019)
In Bali, the majority of the population is Hindu. Hinduism began to flourish in Bali since the 8th century, introduced by Rsi Markandeya (Ardhana, 2002: 62). While Protestant Christianity began to enter the first time to Bali in 1860 through missionaries Van Ect, De Vroom, and Van Der Jagt (Beyer, 2001: 3). Protestant Christian meeting with Hinduism first developed, religious transformation accompanied by harassment. Ulrich Beyer (2001: 5-7) reveals how missionary Tsang To Hang, a Christian and Missionary Alliance (CMA) envoy who obtained permission to come to Bali to baptize the eleven Balinese on 11 November 1931, asking that those who repent willing to burn the divine statues and destroy the family temple, because it is considered to be a place of demons and demons. As a result of this incident, the Balinese Hindu community fell injured feeling and held a defense and resistance against the flow that destroy their sacred traditions.